THE METHODOLOGY FOR THE BUILDING OF THE SUSTAINABILITY MVZ-INDEX BASED ON THE COMMODITIES WITH DUAL PROPERTIES - M. Minchehkov; V. Vodyanova; M. Zapletin (Вестник университета, 2016)
The article presents the main provisions of the model building of the sustainability index on the basis of which it is possible to form the synthetic basic product - the unit of regional currency. The world is ripe the need for changes in financial and currency system. The authors offer a practical approach to a fundamentally new construction of a regional monetary system, based on the methodology of calculation of the new currency unit, secured by the commodities with dual properties.